Influential figures of ancient Rome - Nardo, Don, 1947- (San Diego, Calif. : Lucent Books, 2003)
Profiles influential people who played an important part in the culture and political life in ancient Rome.
Virgil and Livy: shapers of Rome's proud past -- Cato and Cicero: fighting for traditional values -- Augustus and Livia: rulers of a new Rome -- Nero and Agrippina: the corruption and power -- Pliny the Elder and Galen: the pursuit of knowledge -- Hadrian and Antoninus: the good emperors -- Constantine and Ambros: Christianizing the Empire.
Includes bibliographical references : (pages 111-119) and index.
Keywords: Rome -- Biography -- Juvenile literature